2022
DOI: 10.30574/msarr.2022.6.1.0068
|View full text |Cite
|
Sign up to set email alerts
|

Dental phobia: Prevalence and anxiety factors in the city of Mahajanga

Abstract: Introduction: One of the obstacles to dental care in the general population is dental phobia. Fear of the dentist has a negative impact on oral health, as well as the course of dental care. The objective of this study is to determine the prevalence of dental phobias in the Mahajanga’s population. Method: This is a descriptive retrospective cross-sectional study, using the MDSA scale or modified Corah scale. A cluster survey was conducted to constitute the sample. Results: The study population was 210, among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…Authors report that the intensity of anxiety in the face of instrument noise is positively correlated with the occurrence of dental phobia [8,23]. This finding was also reported in this study.…”
Section: Impact Of Dental Anxiety On Oral Healthsupporting
confidence: 90%
See 2 more Smart Citations

State of play of odontophobia in the urban commune of Toliara

Hasina Menja ANDRIAMANJATO,
Njarasoa Charlette RANDRIAMALALA,
Honoria RAKOTOMALALA
et al. 2023
Int. J. Sci. Res. Updates
“…Authors report that the intensity of anxiety in the face of instrument noise is positively correlated with the occurrence of dental phobia [8,23]. This finding was also reported in this study.…”
Section: Impact Of Dental Anxiety On Oral Healthsupporting
confidence: 90%
“…In this study, a significant difference was found between dental phobia and the degree of anxiety about the injection of anesthesia. This result agrees with that of Raciene, as well as Randriamalala et al The authors report that anesthesia is a high risk factor for the occurrence of dental care phobia with p=0.000 [8,18]. This could be explained by the sight of the needle and the pain caused by the injections.…”
Section: Impact Of Dental Anxiety On Oral Healthsupporting
confidence: 90%
See 1 more Smart Citation

State of play of odontophobia in the urban commune of Toliara

Hasina Menja ANDRIAMANJATO,
Njarasoa Charlette RANDRIAMALALA,
Honoria RAKOTOMALALA
et al. 2023
Int. J. Sci. Res. Updates